(METH)acrylic graft copolymer, resin composition, adhesive, and adhesive sheet

The (meth)acrylic graft copolymer addresses the challenge of achieving high adhesive strength and low melt viscosity by incorporating a monomer that forms a crosslinked structure, enhancing the resin composition's adhesive properties.

JP2024175854APending Publication Date: 2024-12-19MITSUBISHI CHEM CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023093904
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-07
Publication Date
2024-12-19

AI Technical Summary

Technical Problem

Existing resin compositions face challenges in achieving high adhesive strength while maintaining low melt viscosity, as seen in Patent Documents 1 and 2.

Method used

A (meth)acrylic graft copolymer with a structural unit derived from a monomer that generates active species upon excitation, having a main chain and side chain structure, where the content of this unit in the side chain exceeds 80% by mass, and includes monomers like benzophenone derivatives, to form a crosslinked structure.

Benefits of technology

The solution provides a resin composition with high adhesive strength and low melt viscosity, balancing both properties effectively.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024175854000001
    Figure 2024175854000001
  • Figure 2024175854000002
    Figure 2024175854000002
  • Figure 2024175854000003
    Figure 2024175854000003
Patent Text Reader

Abstract

To provide: a (meth)acrylic graft copolymer for providing a resin composition with high adhesion while maintaining low melt viscosity; a resin composition; adhesive; and an adhesive sheet.SOLUTION: A (meth)acrylic graft copolymer has a constitutional unit (m) derived from a monomer M that generates active species under excitation to form a crosslinked structure. The (meth)acrylic graft copolymer has a main chain polymer structure and a side chain polymer structure. The content of the constitutional unit (m) in the side chain polymer structure is more than 80 mass% relative to the total mass of the constitutional unit (m) in the (meth)acrylic graft copolymer.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a (meth)acrylic graft copolymer, a resin composition, a pressure-sensitive adhesive, and a pressure-sensitive adhesive sheet. [Background technology]

[0002] A known pressure-sensitive adhesive composition that can be applied to a substrate and is cured by irradiation with ultraviolet light is a resin composition containing a copolymer obtained by polymerizing an alkyl acrylate having an alkyl group with 1 to 4 carbon atoms, an unsaturated carboxylic acid such as acrylic acid, and a benzophenone derivative having a (meth)acryloyloxy group (see, for example, Patent Document 1). Also known are copolymers having structural units derived from benzophenone having a (meth)acryloyloxy group, in which the content of the structural units is 0.01 to 25 mass %, and resin compositions containing the copolymers (see, for example, Patent Document 2). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Laid-Open No. 2006-299017 [Patent Document 2] International Publication No. 2020 / 158475 Summary of the Invention [Problem to be solved by the invention]

[0004] It is difficult to obtain high adhesive strength from the resin composition described in Patent Document 1. The resin composition described in Patent Document 2 has difficulty in achieving a balance between melt viscosity and adhesive strength.

[0005] An object of the present invention is to provide a (meth)acrylic graft copolymer, a resin composition, a pressure-sensitive adhesive, and a pressure-sensitive adhesive sheet that can provide a resin composition having high adhesive strength while maintaining a low melt viscosity. [Means for solving the problem]

[0006] The gist of the present invention is as follows. [1] A (meth)acrylic graft copolymer having a structural unit (m) derived from a monomer M that generates an active species upon excitation and forms a crosslinked structure, The (meth)acrylic graft copolymer has a main chain polymer structure and a side chain polymer structure, A (meth)acrylic graft copolymer, wherein the content of the structural unit (m) contained in the side chain polymer structure is more than 80 mass% based on the total mass of the structural unit (m) contained in the (meth)acrylic graft copolymer. [2] The (meth)acrylic graft copolymer according to [1], which contains a structural unit derived from a macromonomer. [3] The (meth)acrylic graft copolymer according to [1] or [2], wherein the active species is a radical. [4] The (meth)acrylic graft copolymer according to any one of [1] to [3], wherein the monomer M has at least one structure selected from the group consisting of a benzophenone skeleton, a thioxanthone skeleton, and an anthraquinone skeleton. [5] The (meth)acrylic graft copolymer according to any one of [1] to [4], wherein the monomer M is a monomer represented by the following formula (1):

[0007] [ka] (In the formula, R A and R B each independently represents an alkyl group, an alkoxy group, a hydroxyl group, a carboxy group, or a halogen atom; n represents an integer of 0 to 5; m represents an integer of 0 to 4; and X represents a (meth)acryloyloxy group, a (meth)acryloyloxyalkyleneoxy group, or a (meth)acryloyloxyalkyleneoxycarbonyloxy group.

[0008] [6] The (meth)acrylic graft copolymer according to any one of [1] to [5], wherein the content of the structural unit (m) is 0.01% by mass or more and 50% by mass or less, based on the total mass of the (meth)acrylic graft copolymer. [7] The (meth)acrylic graft copolymer according to any one of [1] to [6], wherein the (meth)acrylic graft copolymer has a glass transition temperature of 0°C or lower. [8] The (meth)acrylic graft copolymer according to any one of [1] to [7], wherein the (meth)acrylic graft copolymer contains a structural unit derived from a carboxy group-containing (meth)acrylate. [9] The (meth)acrylic graft copolymer according to [8], wherein the content of the structural units derived from the carboxyl group-containing (meth)acrylate is 0.1% by mass or more and 20% by mass or less, based on the total mass of the (meth)acrylic graft copolymer.

[10] A resin composition comprising the (meth)acrylic graft copolymer according to any one of [1] to [9].

[11] A pressure-sensitive adhesive comprising the resin composition according to

[10] .

[12] A pressure-sensitive adhesive obtained by irradiating the resin composition according to

[10] with ultraviolet light.

[13] An adhesive sheet comprising the adhesive according to

[11] .

[14] An adhesive sheet comprising the adhesive according to

[12] . [Effects of the Invention]

[0009] According to the present invention, it is possible to provide a (meth)acrylic graft copolymer, a resin composition, a pressure-sensitive adhesive, and a pressure-sensitive adhesive sheet that can provide a resin composition having high adhesive strength while maintaining a low melt viscosity. DETAILED DESCRIPTION OF THE INVENTION

[0010] The following definitions of terms apply throughout the specification and claims. "(Meth)acrylate" is a general term for acrylate and methacrylate. "(Meth)acrylic acid" is a general term for acrylic acid and methacrylic acid. The term "(meth)acrylic copolymer" refers to a copolymer in which at least some of the constituent units are derived from a (meth)acrylic monomer. The (meth)acrylic copolymer may further contain a constituent unit derived from a monomer other than the (meth)acrylic monomer (e.g., styrene). "(Meth)acrylic monomer" means a monomer having a (meth)acryloyl group. "(Meth)acryloyl" is a general term for acryloyl and methacryloyl. The term "macromonomer" refers to a polymer having a radically polymerizable group or an addition-reactive functional group. The symbol "to" indicating a range of values ​​means that the values ​​before and after it are included as the lower and upper limits. The number average molecular weight (Mn) and weight average molecular weight (Mw) of the macromonomer and (meth)acrylic copolymer are molecular weights based on polystyrene standards as determined by gel permeation chromatography (GPC).

[0011] The glass transition temperature of a (meth)acrylic copolymer is a calculated value obtained by the Fox formula. For example, when a (meth)acrylic copolymer is composed of a structural unit p derived from a monomer M and a structural unit q derived from a (meth)acrylate, Tg calculated by the following Fox formula from the glass transition temperatures and mass fractions of the respective homopolymers of the monomer M and the (meth)acrylate is taken as the glass transition temperature (unit: °C) of the (meth)acrylic copolymer. 1 / (273+Tg)=Σ(Wi / (273+Tgi)) (In the formula, Wi represents the mass fraction of monomer i, and Tgi represents the glass transition temperature (°C) of the homopolymer of monomer i.)

[0012] The glass transition temperature of the homopolymer of the monomer i can be determined from the value given in Polymer Handbook (J. Brandrup, Interscience, 1989).

[0013] <(Meth)acrylic graft copolymer> The composition of the present invention contains a (meth)acrylic graft copolymer having constitutional units derived from a monomer M that generates active species upon excitation and forms a crosslinked structure.

[0014] A (meth)acrylic graft copolymer is a (meth)acrylic copolymer that is composed of a main chain polymer structure and a side chain polymer structure (branch polymer structure) chemically bonded to the main chain polymer structure (backbone polymer structure). In this specification, a graft copolymer is a polymer having one or more types of blocks connected as side chain polymer structures to the main chain polymer structure. The structures of the main chain polymer and the side chain polymer may be different or the same. There are no particular limitations on the method for producing a graft copolymer. Examples include a method in which a macromonomer having a radically polymerizable double bond at its end is produced as a side chain polymer structure, followed by radical polymerization with a monomer that will become a structural unit of the main chain polymer; a method in which a main chain polymer having a reactive site and a macromonomer having a reactive site are produced in advance, followed by reaction between them; and a method in which, after the main chain polymer is produced, a radical is generated on the main chain polymer using an initiator having hydrogen abstraction ability, and then a monomer that will become a structural unit of the side chain polymer is reacted to produce a side chain polymer structure.

[0015] The (meth)acrylic graft copolymer refers to a graft copolymer in which at least a portion of the constituent units are derived from a (meth)acrylic monomer. The copolymer may further contain constituent units derived from a vinyl radical-polymerizable monomer other than a (meth)acrylic monomer (e.g., styrene). The (meth)acrylic graft copolymer can be produced by copolymerizing a mixture containing a monomer M and a (meth)acrylic monomer. The (meth)acrylic graft copolymer can achieve both high adhesive strength and low melt viscosity by controlling the content of the constituent units derived from the monomer M (hereinafter also referred to as "constituent units (m)") contained in the side chain polymer structure to be more than 80% by mass relative to the total mass of the constituent units (m) contained in the (meth)acrylic graft copolymer.

[0016] The total mass of the structural units (m) contained in the side chain polymer structure is more than 80% by mass, preferably 90% by mass or more, more preferably 95% by mass or more, even more preferably 98% by mass or more, and particularly preferably 100% by mass, relative to the total mass of the structural units (m) contained in the (meth)acrylic graft copolymer.

[0017] The total mass of the structural units (m) contained in the main chain polymer structure is preferably less than 20% by mass, more preferably 10% by mass or less, even more preferably 5% by mass or less, particularly preferably 2% by mass or less, and most preferably 0% by mass, relative to the total mass of the structural units (m) contained in the (meth)acrylic graft copolymer.

[0018] When the structural unit (m) is contained in both the side chain polymer structure and the main chain polymer structure, the mass ratio expressed as [the total mass (% by mass) of the structural units (m) contained in the side chain polymer structure relative to the total mass of the structural units (m) contained in the (meth)acrylic graft copolymer] / [the total mass (% by mass) of the structural units (m) contained in the main chain polymer structure relative to the total mass of the structural units (m) contained in the (meth)acrylic graft copolymer] is preferably greater than 0.56, more preferably from 0.6 to 100, and even more preferably from 1.0 to 100.

[0019] The difference expressed as [the total mass (% by mass) of the structural units (m) contained in the side chain polymer structure relative to the total mass of the structural units (m) contained in the (meth)acrylic graft copolymer] - [the total mass (% by mass) of the structural units (m) contained in the main chain polymer structure relative to the total mass of the structural units (m) contained in the (meth)acrylic graft copolymer] is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, and even more preferably 0.10% by mass or more, with the upper limit usually being 10% by mass.

[0020] The mass ratio represented by [total mass of structural units contained in the side chain polymer structure] / [total mass of structural units contained in the main chain polymer structure] is preferably 0.01 to 0.5, more preferably 0.03 to 0.3, and even more preferably 0.05 to 0.1.

[0021] The content of the structural unit (m) contained in the side chain polymer structure is preferably 0.1% by mass or more and 30% by mass or less, more preferably 0.3% by mass or more and 20% by mass or less, even more preferably 0.5% by mass or more and 10% by mass or less, and particularly preferably 1.0% by mass or more and 5.0% by mass or less, relative to the total mass of the side chain polymer structure. When the content of the structural unit (m) relative to the total mass of the side chain polymer structure is equal to or greater than the lower limit, it becomes easier to achieve both high adhesive strength and low melt viscosity. When the content of the structural unit (m) relative to the total mass of the side chain polymer structure is equal to or less than the upper limit, it becomes easier to achieve a balance of adhesive performance.

[0022] The (meth)acrylic graft copolymer does not substantially have a radically polymerizable group at its terminal. The term "radical polymerizable group" means a group having a radically polymerizable unsaturated bond, and includes ethylenically unsaturated groups such as a (meth)acryloyl group and a vinyl group.

[0023] "Constituent units derived from monomer M" The monomer M generates active species upon photoexcitation by ultraviolet light, electron beams, etc., and forms a crosslinked structure. Examples of the active species include radicals, cations, and anions, with radicals being preferred from the viewpoint of reactivity. Examples of monomers that generate radicals upon photoexcitation include monomers having a benzophenone skeleton, a thioxanthone skeleton, an anthraquinone skeleton, etc. Since these skeletons contain a benzophenone skeleton, photoexcitation generates an excited triplet state of the benzophenone skeleton, which then abstracts hydrogen from the hydrocarbon group to form carbon radical A having a secondary hydroxyl group. This carbon radical A is thought to bond with carbon radical B generated by hydrogen abstraction, thereby forming a crosslinked structure having a tertiary hydroxyl group and two phenyl groups at the crosslinking point. The crosslinked structure preferably contains, for example, a diphenylhydroxymethyl group. The phenyl group in the crosslinked structure may or may not have a substituent. As the monomer M, a benzophenone derivative represented by the following formula (1) is preferred in terms of reactivity.

[0024] [ka]

[0025] In formula (1), R A and R B each independently represents an alkyl group, an alkoxy group, a hydroxyl group, a carboxyl group, or a halogen atom. The alkyl group is preferably a linear or branched alkyl group having 1 to 30 carbon atoms, more preferably a linear or branched alkyl group having 1 to 10 carbon atoms, and even more preferably a linear or branched alkyl group having 1 to 5 carbon atoms. The alkoxy group is preferably a linear or branched alkoxy group having 1 to 30 carbon atoms, more preferably a linear or branched alkoxy group having 1 to 10 carbon atoms, and even more preferably a linear or branched alkoxy group having 1 to 5 carbon atoms. Halogen atoms include fluorine atoms, chlorine atoms, bromine atoms, and iodine atoms. n is an integer of 0 to 5, preferably an integer of 0 to 3, and more preferably 0. m is an integer of 0 to 4, preferably an integer of 0 to 3, and more preferably 0. X represents a (meth)acryloyloxy group, a (meth)acryloyloxyalkyleneoxy group, or a (meth)acryloyloxyalkyleneoxycarbonyloxy group. The alkylene group in the (meth)acryloyloxyalkyleneoxy group is preferably an alkylene group having 2 to 10 carbon atoms, and more preferably an alkylene group having 2 to 6 carbon atoms. Examples of the (meth)acryloyloxyalkyleneoxy group include a 2-(meth)acryloyloxyethoxy group and a 2-(meth)acryloyloxypropoxy group. Examples of the (meth)acryloyloxyalkyleneoxycarbonyloxy group include a 4-(meth)acryloyloxybutoxycarbonyloxy group.

[0026] Examples of the monomer represented by the above formula (1) include 4-acryloyloxybenzophenone, 4-methacryloyloxybenzophenone, 4-[2-(acryloyloxy)ethoxy]benzophenone, 4-[2-(methacryloyloxy)ethoxy]benzophenone, 2-hydroxy-4-acryloyloxybenzophenone, 2-hydroxy-4-methacryloyloxybenzophenone, and 2-hydroxy-4-(2-acryloyloxy)ethoxybenzophenone. Examples of suitable benzophenones include 2-hydroxy-4-(2-methyl-2-acryloyloxy)ethoxybenzophenone, 2-hydroxy-4-acryloyloxy-5-tert-butylbenzophenone, 2-hydroxy-4-acryloyloxy-2',4'-dichlorobenzophenone, 4-(((4-benzoylphenoxy)carbonyl)oxy)butyl acrylate, and 4-(((4-benzoylphenoxy)carbonyl)oxy)butyl methacrylate. Of these, 4-methacryloyloxybenzophenone and 4-[2-(methacryloyloxy)ethoxy]benzophenone are preferred. The monomer M may be used alone or in combination of two or more kinds.

[0027] The content of the structural unit (m) is preferably 0.01 to 50% by mass, more preferably 0.02 to 1.00% by mass, even more preferably 0.03 to 0.50% by mass, and particularly preferably 0.05 to 0.30% by mass, relative to the total mass of the (meth)acrylic graft copolymer. When the content of the structural unit (m) is equal to or greater than the lower limit, crosslinking efficiency is improved. When the content of the structural unit (m) is equal to or less than the upper limit, it is easy to achieve a balance between high adhesive strength and low melt viscosity.

[0028] "Structural units derived from (meth)acrylic monomers" The (meth)acrylic graft copolymer of the present invention may contain a (meth)acrylic monomer, such as a hydrocarbon group-containing (meth)acrylate, a hydroxyl group-containing (meth)acrylate, a carboxyl group-containing (meth)acrylate, an amino group-containing (meth)acrylate, an epoxy group-containing (meth)acrylate, or a polyfunctional (meth)acrylate. As the (meth)acrylic monomer, one type may be used alone, or two or more types may be used in combination.

[0029] Examples of hydrocarbon group-containing (meth)acrylates include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, phenyl (meth)acrylate, benzyl (meth)acrylate, cyclohexyl (meth)acrylate, and isobornyl (meth)acrylate.

[0030] Examples of hydroxyl group-containing (meth)acrylates include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate.

[0031] Examples of carboxy group-containing (meth)acrylates include (meth)acrylic acid, 2-(meth)acryloyloxyethylhexahydrophthalic acid, 2-(meth)acryloyloxypropylhexahydrophthalic acid, and 2-(meth)acryloyloxyethylphthalic acid.

[0032] Examples of amino group-containing (meth)acrylates include dimethylaminoethyl (meth)acrylate and diethylaminoethyl (meth)acrylate.

[0033] An example of the epoxy group-containing (meth)acrylate is glycidyl (meth)acrylate.

[0034] Examples of polyfunctional (meth)acrylates include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, and polyethylene glycol di(meth)acrylate.

[0035] The (meth)acrylic graft copolymer may contain, as a structural unit derived from a hydrocarbon group-containing (meth)acrylate, a structural unit derived from an alkyl (meth)acrylate having a linear alkyl group having 1 to 30 carbon atoms or a branched alkyl group having 3 to 30 carbon atoms. The linear alkyl group having 1 to 30 carbon atoms preferably has 2 to 10 carbon atoms, more preferably 3 to 8 carbon atoms, and even more preferably 4 carbon atoms.

[0036] The content of the structural units derived from the carboxyl group-containing (meth)acrylate is preferably 0.1% by mass or more and 20% by mass or less, more preferably 0.5% by mass or more and 10% by mass or less, even more preferably 1% by mass or more and 8% by mass or less, and particularly preferably 3% by mass or more and 6% by mass or less, relative to the total mass of the (meth)acrylic graft copolymer. When the content of the structural units derived from the carboxyl group-containing (meth)acrylate is equal to or greater than the lower limit, it becomes easier to achieve both high adhesive strength and low melt viscosity. When the content of the structural units derived from the carboxyl group-containing (meth)acrylate is equal to or less than the upper limit, it becomes easier to achieve a balance of adhesive performance.

[0037] "Structural units derived from macromonomers" The (meth)acrylic graft copolymer in the present invention preferably contains a structural unit derived from a macromonomer.

[0038] The structural units derived from the macromonomer are preferably contained in the side chain polymer of the (meth)acrylic graft copolymer (however, among the structural units derived from the macromonomer, it is preferred that only the structural units derived from the structural units having a radically polymerizable double bond at the terminal be contained in the main chain polymer).

[0039] The macromonomer is preferably a macromonomer represented by the following formula (2).

[0040] [ka]

[0041] In the above formula (2), R represents a hydrogen atom, an alkyl group, an alicyclic group, an aryl group, or a heterocyclic group. These groups may have a substituent. Examples of the alkyl group in R include a branched or linear alkyl group having 1 to 30 carbon atoms. Examples of the alicyclic group may be monocyclic or polycyclic, and include an alicyclic group having 3 to 20 carbon atoms. Examples of the aryl group include an aryl group having 6 to 18 carbon atoms. Examples of the heterocyclic group include a heterocyclic group having 5 to 18 carbon atoms. Examples of the substituent include an alkyl group, an aryl group, a carboxy group, an alkoxycarbonyl group, a cyano group, a hydroxy group, an alkoxy group, an amino group, a monomethylamino group, a dimethylamino group, a carbamoyl group, an N-methylcarbamoyl group, an N,N-dimethylcarbamoyl group, a halogen atom, an allyl group, an epoxy group, a siloxy group, an alkali salt of a carboxy group, an alkali salt of a sulfoxy group, a polyethylene oxide group, a polypropylene oxide group, and a quaternary ammonium salt group.

[0042] R is preferably an alkyl group or a saturated alicyclic group, and more preferably an alkyl group, a saturated alicyclic group, or a saturated alicyclic group having an alkyl group as a substituent. Among these, from the viewpoint of availability, a methyl group, an ethyl group, an n-propyl group, an i-propyl group, an n-butyl group, an i-butyl group, a t-butyl group, a pentyl group, a hexyl group, a heptyl group, an octyl group, a cyclopropyl group, a cyclobutyl group, an isobornyl group, and an adamantyl group are more preferred, and a methyl group, an ethyl group, an n-propyl group, an i-propyl group, an n-butyl group, an i-butyl group, a t-butyl group, a cyclopropyl group, a cyclobutyl group, an isobornyl group, and an adamantyl group are even more preferred.

[0043] In formula (2), Z is a terminal group, and examples thereof include a hydrogen atom and a group derived from a radical polymerization initiator, similar to the terminal groups of polymers obtained by known radical polymerization. R 21 is a hydrogen atom or a methyl group. R 22is an unsubstituted or substituted alkyl group, an unsubstituted or substituted alicyclic group, an unsubstituted or substituted aryl group, an unsubstituted or substituted heteroaryl group, an unsubstituted or substituted aralkyl group, an unsubstituted or substituted alkaryl group, an unsubstituted or substituted organosilyl group, or an unsubstituted or substituted (poly)organosiloxane group. The substituents in these groups are each at least one selected from the group consisting of alkyl groups, aryl groups, heteroaryl groups, non-aromatic heterocyclic groups, aralkyl groups, alkaryl groups, carboxylic acid groups, carboxylic acid ester groups, epoxy groups, hydroxy groups, alkoxy groups, primary amino groups, secondary amino groups, tertiary amino groups, isocyanato groups, sulfonic acid groups, and halogen atoms. a is a natural number of 2 or greater. a is within the range such that the weight-average molecular weight (Mw) of the macromonomer is 500 or greater and 100,000 or less. a R 21 may all be the same or some may be different. 22 may all be the same or some may be different. As the macromonomer, one type may be used alone, or two or more types may be used in combination.

[0044] The Mw of the macromonomer is preferably 500 to 100,000, more preferably 600 to 50,000, and even more preferably 1,000 to 20,000. When the Mw of the macromonomer is within the above range, a good balance between adhesive strength and handling properties (compatibility with other components, coatability, hot-melt processability, etc.) tends to be achieved.

[0045] The Mn of the macromonomer is preferably 500 to 50,000, more preferably 600 to 20,000, and even more preferably 1,000 to 10,000. When the Mn of the macromonomer is within the above range, a good balance between adhesive strength and handling properties (compatibility with other components, coatability, hot-melt processability, etc.) tends to be achieved.

[0046] The macromonomer may be produced by a known method or may be commercially available. Examples of the method for producing the macromonomer include a method using a cobalt chain transfer agent, a method using an α-substituted unsaturated compound such as α-methylstyrene dimer as a chain transfer agent, a method using an initiator, a method of chemically bonding a radical polymerizable group to a polymer, and a method using thermal decomposition. In producing the macromonomer, the monomer is not particularly limited, and examples thereof include the above-mentioned monomer M and (meth)acrylic monomers. As the monomer, one type may be used alone, or two or more types may be used in combination.

[0047] The content of the structural units derived from the macromonomer is preferably 0.1% by mass or more and 40% by mass or less, more preferably 0.3% by mass or more and 30% by mass or less, even more preferably 0.5% by mass or more and 20% by mass or less, and particularly preferably 1.0% by mass or more and 10% by mass or less, relative to the total mass of the (meth)acrylic graft copolymer. When the content of the structural units derived from the macromonomer is equal to or greater than the lower limit, it becomes easier to achieve both high adhesive strength and low melt viscosity. When the content of the structural units derived from the macromonomer is equal to or less than the upper limit, it becomes easier to achieve a balance of adhesive performance.

[0048] The content of the structural unit (m) contained in the macromonomer is preferably 0.1% by mass or more and 50% by mass or less, more preferably 0.3% by mass or more and 40% by mass or less, even more preferably 0.5% by mass or more and 30% by mass or less, particularly preferably 1.0% by mass or more and 20% by mass or less, and most preferably 2.0% by mass or more and 10% by mass or less, relative to the total mass of the macromonomer. When the content of the structural unit (m) relative to the total mass of the macromonomer is equal to or greater than the lower limit, it becomes easier to achieve both high adhesive strength and low melt viscosity. When the content of the structural unit (m) relative to the total mass of the macromonomer is equal to or less than the upper limit, it becomes easier to achieve a balance of adhesive performance.

[0049] The (meth)acrylic graft copolymer of the present invention may contain, in addition to the above-mentioned structural units, structural units derived from other monomers.

[0050] The other monomers are not particularly limited, and examples thereof include styrene, crotonic acid, fumaric acid, maleic acid, itaconic acid, maleic anhydride, itaconic anhydride, (meth)acrylamide, (meth)acrylonitrile, vinyl chloride, vinyl acetate, vinyl fluoride, and vinylidene fluoride. As the other monomer, one type may be used alone, or two or more types may be used in combination.

[0051] The Mw of the (meth)acrylic graft copolymer is preferably 10,000 to 2,000,000, more preferably 11,000 to 1,000,000, even more preferably 30,000 to 600,000, particularly preferably 50,000 to 500,000, and most preferably 100,000 to 400,000. When the Mw of the (meth)acrylic graft copolymer is at least the lower limit, the adhesive layer has excellent durability. When the Mw of the (meth)acrylic graft copolymer is at most the upper limit, the adhesive layer has excellent handleability (compatibility with other components, coatability, hot-melt processability, etc.). For the same reasons as for Mw, the number average molecular weight (Mn) of the (meth)acrylic graft copolymer is preferably 10,000 to 1,000,000, more preferably 11,000 to 500,000, still more preferably 12,000 to 100,000, and particularly preferably 13,000 to 50,000. For the same reasons as for Mw, Mw / Mn of the (meth)acrylic graft copolymer is preferably from 1.0 to 20.0, more preferably from 3.0 to 17.0, even more preferably from 4.0 to 15.0, and particularly preferably from 5.0 to 13.0.

[0052] From the viewpoint of adhesiveness, the glass transition temperature (Tg) of the (meth)acrylic graft copolymer is preferably 0° C. or lower, more preferably −5° C. or lower. The lower limit of Tg of the (meth)acrylic graft copolymer is not particularly limited, but may be, for example, −100° C. or higher.

[0053] The (meth)acrylic graft copolymer can be produced by a known method using a known polymerization initiator. Examples of the polymerization method include solution polymerization, suspension polymerization, bulk polymerization, and emulsion polymerization, among which solution polymerization is preferred. A radical polymerization initiator is preferred as the polymerization initiator. Examples of the solvent used in solution polymerization include organic solvents such as acetone, toluene, xylene, and ethyl acetate.

[0054] The composition of the present invention described above can achieve both adhesive strength and low melt viscosity by adjusting the content of the structural unit (m) contained in the side chain polymer structure to more than 80 mass% relative to the total mass of the structural unit (m) contained in the (meth)acrylic graft copolymer.

[0055] <Resin composition> The resin composition of the present invention contains the (meth)acrylic graft copolymer of the present invention. The content of the (meth)acrylic graft copolymer is preferably 20 to 100 mass%, more preferably 30 to 100 mass%, even more preferably 40 to 100 mass%, and particularly preferably 50 to 100 mass%, relative to the total mass of the resin composition.

[0056] The resin composition of the present invention may contain components other than the (meth)acrylic graft copolymer, including, but not limited to, a solvent, a filler, a crosslinking agent, a tackifier resin, an antioxidant, a light stabilizer, a metal deactivator, an antioxidant, a moisture absorbent, a rust inhibitor, a hydrolysis inhibitor, and a reaction catalyst. The resin composition of the present invention may be in the form of a liquid composition containing a solvent, or may be in the form of a composition containing no solvent.

[0057] The melt viscosity at 130° C. of the resin composition of the present invention before irradiation is preferably 160 Pa·s or less, more preferably 20 to 160 Pa·s, and even more preferably 30 to 158 Pa·s. The melt viscosity at 130°C before irradiation can be measured by the method described in the Examples.

[0058] The adhesive strength of the resin composition of the present invention after curing is preferably 9.5 N / 25 mm or more, more preferably 9.5 to 20.0 N / 25 mm, and even more preferably 9.5 to 15.0 N / 25 mm. The adhesive strength of the resin composition after curing can be measured by the method described in the examples.

[0059] <Adhesives, adhesive sheets> The pressure-sensitive adhesive of the present invention is a pressure-sensitive adhesive comprising the resin composition of the present invention. The pressure-sensitive adhesive of the present invention may be the resin composition of the present invention used in an uncured state, or may be the resin composition cured by irradiation with active energy rays. As the active energy rays, ultraviolet rays are preferred from the viewpoint of versatility. The pressure-sensitive adhesive of the present invention may be a hot-melt type pressure-sensitive adhesive, preferably a reactive hot-melt type pressure-sensitive adhesive, and more preferably an ultraviolet-reactive hot-melt type pressure-sensitive adhesive.

[0060] The pressure-sensitive adhesive sheet of the present invention is a pressure-sensitive adhesive sheet containing the pressure-sensitive adhesive of the present invention, and has a pressure-sensitive adhesive layer made of the pressure-sensitive adhesive of the present invention. The pressure-sensitive adhesive layer may be made of a resin composition, or may be made of a cured product obtained by irradiating a resin composition with ultraviolet light. In terms of handleability of the pressure-sensitive adhesive sheet, a pressure-sensitive adhesive layer made of a cured product obtained by curing a resin composition with ultraviolet light is preferred. The ultraviolet light irradiation dose is 20 to 150 mJ / cm. 2 is preferably 30 to 130 mJ / cm 2 More preferably, it is 35 to 105 mJ / cm 2 It is more preferable that:

[0061] The pressure-sensitive adhesive sheet of the present invention may be in an embodiment consisting of only a pressure-sensitive adhesive layer formed by molding the resin composition of the present invention into a sheet, or may be in an embodiment of a laminate formed by molding the resin composition of the present invention into a sheet and laminating a different pressure-sensitive adhesive layer on one or both sides of the pressure-sensitive adhesive layer, or may be in an embodiment of a laminate formed by molding the resin composition of the present invention into a sheet and laminating a release substrate on one or both sides of the pressure-sensitive adhesive layer.

[0062] The thickness of the pressure-sensitive adhesive layer can be appropriately set depending on the application, and is preferably 10 to 500 μm, more preferably 20 to 100 μm.

[0063] The uses of the pressure-sensitive adhesive sheet of the present invention are not particularly limited. For example, by applying it to a transparent plastic film or processing it into a pressure-sensitive adhesive film, it can be used for laminating window films for vehicles, buildings, etc., laminating labels in label displays, laminating decorative films, etc. By forming a pressure-sensitive adhesive sheet on a substrate, it can be used as a tape. Furthermore, by processing it into a transparent double-sided pressure-sensitive adhesive sheet, it can be used for laminating various panels in display displays such as liquid crystal panels, laminating transparent plate materials such as glass, etc. [Example]

[0064] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to the following descriptions. In the following descriptions, "parts" means "parts by mass."

[0065] <Abbreviation> The abbreviations for the raw materials used in this example are shown below. IPA: Isopropyl alcohol. MMA: methyl methacrylate. 4-MBP: 4-methacryloyloxybenzophenone. n-BA: n-butyl acrylate. AA: acrylic acid. EHMA: 2-ethylhexyl methacrylate. iBMA: isobutyl methacrylate. AMBN: 2,2'-azobis(2-methylbutyronitrile). V-65: 2,2'-Azobis(2,4-dimethylvaleronitrile).

[0066] <Molecular weight of polymer X> Measurement was performed using a gel permeation chromatography (GPC) apparatus (HLC-8320, manufactured by Tosoh Corporation). A 0.2% by mass solution of polymer X in tetrahydrofuran (THF) was prepared, and 10 μL of the solution was injected into an apparatus equipped with columns manufactured by Tosoh Corporation (TSKgel SuperHZM-M (inner diameter 4.6 mm, length 15 cm), HZM-M (inner diameter 4.6 mm, length 15 cm), HZ-2000 (inner diameter 4.6 mm, length 15 cm), TSKguardcolumn SuperHZ-L (inner diameter 4.6 mm, length 3.5 cm)). Measurement was performed under conditions of a flow rate of 0.35 mL / min, eluent: tetrahydrofuran (stabilizer: butylhydroxytoluene (BHT)), and column temperature: 40°C, and the number average molecular weight (Mn) of polymer X was calculated in terms of standard polystyrene.

[0067] <Tg of polymer A> The Tg of polymer A was calculated by the above Fox formula. <Molecular weight of polymer A> Measurement was performed using a gel permeation chromatography (GPC) system (HLC-8320, manufactured by Tosoh Corporation). A 0.27% by mass solution of polymer A in tetrahydrofuran (THF) was prepared, and 10 μL of the solution was injected into the system equipped with columns manufactured by Tosoh Corporation (TSKgel SuperHZMH (inner diameter 4.6 mm, length 15 cm), HZMH (inner diameter 4.6 mm, length 15 cm), TSKguardcolumn SuperHZ-H (inner diameter 4.6 mm, length 3.5 cm)). Measurement was performed under conditions of a flow rate of 0.5 mL / min, eluent: THF (stabilizer: butylhydroxytoluene (BHT)), and column temperature: 40°C, and the weight average molecular weight (Mw), number average molecular weight (Mn), and Mw / Mn of polymer A were calculated in terms of standard polystyrene.

[0068] <Melt viscosity> The resin composition obtained in each example was diluted with ethyl acetate to a solid content of 33.3% by mass, and after visually confirming that no polymer remained dissolved, the resin composition was made into a liquid at room temperature (23°C). The resin composition was applied to a release-treated PET film using an applicator and dried at 90°C for 1 hour to form an adhesive layer with a thickness of 50 μm. The melt viscosity of the adhesive layer was measured using a HAAKE MARS viscoelasticity measuring device. The viscosity (η * ) was taken as the melt viscosity at 130°C before irradiation.

[0069] <Preparation of test specimens> The resin composition obtained in each example was diluted with ethyl acetate to a solids content of 33.3% by mass, and after visually confirming that no undissolved polymer remained, the resin composition was made liquid at room temperature (23°C). The resin composition was applied to a 38 μm-thick PET film using an applicator and dried at 90°C for 1 hour to form an adhesive layer. Using an 85 mW high-pressure mercury lamp, the PET film (PET) on which the adhesive layer was formed was irradiated with ultraviolet light (UV-C) in the air to cure the adhesive layer. The UV-C irradiation dose was 35 mJ / cm. 2 The measured values ​​were measured using an integrating light meter UV POWER PUCK II (S / N 13685) (manufactured by EIT, USA). A release-treated PET film (release PET) was placed on top of the laminate to obtain a laminate with a release PET-adhesive layer-PET structure. The thickness of the adhesive layer was 50 μm. After curing, the laminate was cut into strips 25 mm wide and 250 mm long to prepare test specimens.

[0070] <Adhesive strength> The PET peeling film was peeled off from the test piece to expose the adhesive layer, and the test piece was then attached to a 30mm x 110mm stainless steel (SUS) plate using a 3kg hand roller so that the bonded surface was 25mm x 70mm. The peel strength (N / 25mm) against the SUS plate was measured at a peel angle of 180° and a tensile speed of 300mm / min, and this was taken as the adhesive strength.

[0071] <Production Example 1> A polymerization apparatus equipped with a stirrer, condenser, thermometer, and nitrogen gas inlet tube was charged with 900 parts of deionized water, 60 parts of 2-sulfoethyl sodium methacrylate, 10 parts of potassium methacrylate, and 12 parts of MMA, and the contents were stirred. The temperature was raised to 50°C while the atmosphere inside the polymerization apparatus was replaced with nitrogen. Furthermore, 0.08 parts of 2,2'-azobis(2-methylpropionamidine) dihydrochloride was added as a polymerization initiator, and the temperature was raised to 60°C. After the temperature was raised, MMA was continuously added dropwise using a dropping pump at a rate of 0.24 parts / min for 75 minutes. The mixture was held at 60°C for 6 hours and then cooled to room temperature to obtain Dispersant 1 with a solids content of 10% by mass.

[0072] <Production Example 2> In a synthesis apparatus equipped with a stirrer, 1.00 g of cobalt(II) acetate tetrahydrate, 1.93 g of diphenylglyoxime, and 80 mL of diethyl ether (previously deoxygenated by nitrogen bubbling) were added under a nitrogen atmosphere and stirred at room temperature for 30 minutes. 10 mL of boron trifluoride diethyl etherate was then added and stirred for 6 hours. The mixture was filtered, and the solid was washed with diethyl ether and dried in vacuo for 15 hours to obtain 2.12 g of chain transfer agent 1 as a reddish-brown solid.

[0073] <Production Example 3> In a polymerization apparatus equipped with a stirrer, a condenser, a thermometer, and a nitrogen gas inlet tube, 145 parts of deionized water, 0.1 parts of sodium sulfate, and 0.5 parts of dispersant 1 (solid content 10% by mass) were placed and stirred to form a homogeneous aqueous solution. Further, 97.2 parts of MMA, 2.8 parts of 4-MBP, 0.0022 parts of chain transfer agent 1, and 0.5 parts of Perocta® O (1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate, manufactured by NOF Corporation) as a polymerization initiator were added to form an aqueous suspension. The inside of the polymerization reactor was then purged with nitrogen, the temperature was raised to 80°C, and the mixture was stirred for 3.5 hours, and then, in order to further increase the polymerization rate, the temperature was raised to 90°C and maintained at that temperature for 1 hour. After that, the mixture was cooled to 40°C, and the resulting aqueous suspension was filtered. The residue remaining on the filter was washed with deionized water, dehydrated, and dried at 40°C for 16 hours to obtain Polymer X-1.

[0074] <Production Examples 4-5, Production Examples 8-9> Polymers X-2 to X-3 and X-6 to X-7 were produced in the same manner as in Production Example 3, except that the formulation was changed as shown in Table 1.

[0075] <Production Example 6> A four-neck flask equipped with a stirrer, thermometer, condenser, and nitrogen gas inlet was charged with 87.2 parts of MMA, 10 parts of EHMA, 2.8 parts of 4-MBP, 0.00078 parts of chain transfer agent 1, and 58 parts of ethyl acetate. Oxygen was purged by nitrogen bubbling. Next, 0.4 parts of AMBN as a polymerization initiator and 2 parts of ethyl acetate were added. The external temperature was then raised to 90°C in a water bath, and the reaction was allowed to proceed under reflux for 2 hours. Next, 0.3 parts of V-65 and 20 parts of ethyl acetate were added dropwise over 1 hour, and the mixture was then maintained under reflux for another 2 hours. The reaction solution was then cooled to 40°C to obtain a solution containing polymer X-4. Ethyl acetate was added to this solution to adjust the nonvolatile content to 50% by mass.

[0076] <Production Example 7> A solution containing polymer X-5 was produced in the same manner as in Production Example 6, except that the formulation was changed as shown in Table 1.

[0077] [Table 1]

[0078] Example 1 A reaction vessel equipped with a stirrer, thermometer, condenser, and nitrogen gas inlet was charged with 40 parts of ethyl acetate and 5.7 parts of IPA, and the external temperature was raised to 85°C under nitrogen gas flow. After the external temperature reached 85°C and the internal temperature stabilized, a mixture consisting of 25 parts of ethyl acetate, 5 parts of Polymer X-1, 89.9 parts of n-BA, 5.1 parts of AA, and 0.13 parts of Niper (registered trademark) BMT-K40 (NOF Corp., trade name) was added dropwise over 4 hours. After the dropwise addition was completed and the mixture was held for 1 hour, a mixture consisting of 0.5 parts of Perocta (registered trademark) O and 10 parts of ethyl acetate was added over 30 minutes. After that, after holding for 2 hours, 0.5 parts of an antioxidant (manufactured by BASF, product name "Irganox (registered trademark) 1010") was added, and ethyl acetate was added so that the solid content (the ratio of the amount of monomer charged to the amount of (monomer + solvent charged)) became 53 mass%, and then the mixture was cooled to room temperature to obtain a copolymer solution A-1 containing copolymer A-1.

[0079] <Examples 2 to 5> <Comparative Examples 1 and 2> Polymers A-2 to A-7 were produced in the same manner as in Example 1, except that the formulation was changed as shown in Table 2.

[0080] Table 2 shows the measurement results of Tg, molecular weight, melt viscosity and adhesive strength of polymers A-1 to A-7.

[0081] [Table 2]

[0082] As shown in Table 2, polymers A-1 to A-5, which are (meth)acrylic graft copolymers having a structural unit (m) derived from monomer M, and in which the content of the structural unit (m) contained in the side chain polymer structure is more than 80 mass% relative to the total mass of the structural unit (m) contained in the (meth)acrylic graft copolymer, were excellent in both adhesive strength and melt viscosity. Polymer A-6, which contains the structural unit (m) derived from monomer M only in the main chain polymer structure and the content of the structural unit (m) contained in the side chain polymer structure is 80 mass% or less relative to the total mass of the structural unit (m) contained in the (meth)acrylic graft copolymer, had a high melt viscosity and insufficient adhesive strength. Polymer A-7, which contains a structural unit (m) derived from monomer M in both the main chain polymer structure and the side chain polymer structure, and in which the content of the structural unit (m) in the side chain polymer structure is 80 mass% or less relative to the total mass of the structural unit (m) contained in the (meth)acrylic graft copolymer, had a high melt viscosity and insufficient adhesive strength. [Industrial Applicability]

[0083] According to the present invention, it is possible to provide a (meth)acrylic graft copolymer, a resin composition, a pressure-sensitive adhesive, and a pressure-sensitive adhesive sheet for providing a resin composition having high adhesive strength while maintaining a low melt viscosity.

Claims

1. A (meth)acrylic graft copolymer having a structural unit (m) derived from a monomer M that generates an active species upon excitation and forms a crosslinked structure, The (meth)acrylic graft copolymer has a main chain polymer structure and a side chain polymer structure, A (meth)acrylic graft copolymer, wherein the content of the structural unit (m) contained in the side chain polymer structure is more than 80 mass% based on the total mass of the structural unit (m) contained in the (meth)acrylic graft copolymer.

2. The (meth)acrylic graft copolymer according to claim 1 , which contains a structural unit derived from a macromonomer.

3. The (meth)acrylic graft copolymer according to claim 1 , wherein the active species is a radical.

4. The (meth)acrylic graft copolymer according to claim 1 , wherein the monomer M has at least one structure selected from the group consisting of a benzophenone skeleton, a thioxanthone skeleton, and an anthraquinone skeleton.

5. The (meth)acrylic graft copolymer according to claim 1 , wherein the monomer M is a monomer represented by the following formula (1): 【Chemistry 1】 (In the formula, R A and R B each independently represents an alkyl group, an alkoxy group, a hydroxyl group, a carboxy group, or a halogen atom, n represents an integer of 0 to 5, m represents an integer of 0 to 4, and X represents a (meth)acryloyloxy group, a (meth)acryloyloxyalkyleneoxy group, or a (meth)acryloyloxyalkyleneoxycarbonyloxy group.

6. The (meth)acrylic graft copolymer according to claim 1, wherein the content of the structural unit (m) is 0.01% by mass or more and 50% by mass or less, based on the total mass of the (meth)acrylic graft copolymer.

7. The (meth)acrylic graft copolymer according to claim 1 , wherein the (meth)acrylic graft copolymer has a glass transition temperature of 0° C. or lower.

8. The (meth)acrylic graft copolymer according to claim 1 , which contains a structural unit derived from a carboxy group-containing (meth)acrylate.

9. The (meth)acrylic graft copolymer according to claim 8, wherein the content of the structural unit derived from the carboxy group-containing (meth)acrylate is 0.1 mass% or more and 20 mass% or less with respect to the total mass of the (meth)acrylic graft copolymer.

10. A resin composition comprising the (meth)acrylic graft copolymer according to any one of claims 1 to 9.

11. A pressure-sensitive adhesive comprising the resin composition according to claim 10.

12. A pressure-sensitive adhesive obtained by irradiating the resin composition according to claim 10 with ultraviolet light.

13. A pressure-sensitive adhesive sheet comprising the pressure-sensitive adhesive according to claim 11.

14. A pressure-sensitive adhesive sheet comprising the pressure-sensitive adhesive according to claim 12.

Citation Information

Patent Citations

  • UV ray-curable adhesive composition and adhesive sheet using the same

    JP2006299017A

  • (METH)acrylic copolymer, pressure-sensitive adhesive composition, pressure-sensitive adhesive, and pressure-sensitive adhesive sheet

    WO2020158475A1